2013
DOI: 10.1073/pnas.1314984111
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and modeling of mitotic spindle orientations in three dimensions

Abstract: The orientation of the mitotic spindle determines the relative size and position of the daughter cells and influences the asymmetric inheritance of localized cell fate determinants. The onset of mammalian neurogenesis, for example, coincides with changes in spindle orientation. To address the functional implications of this and related phenomena, precise methods for determining the orientation of the mitotic spindle in complex tissues are needed. Here, we present methodology for the analysis of spindle orienta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 33 publications
4
41
0
Order By: Relevance
“…Our 3D en face analysis (Juschke et al, 2014) excludes mitotic spindle orientation as a major mechanism in Wdr62 and Aspm mutant mice, as we detected no difference in neural progenitor spindle orientation between WT, Wdr62 +/−; Aspm −/− and Wdr62 −/− embryos, suggesting that other mechanisms contribute to the microcephaly observed in these mutants. Our finding that Aspm and Wdr62 function together to promote centriole duplication provides a novel insight into how defects in centriole biogenesis may underlie the pathogenesis of MCPH.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Our 3D en face analysis (Juschke et al, 2014) excludes mitotic spindle orientation as a major mechanism in Wdr62 and Aspm mutant mice, as we detected no difference in neural progenitor spindle orientation between WT, Wdr62 +/−; Aspm −/− and Wdr62 −/− embryos, suggesting that other mechanisms contribute to the microcephaly observed in these mutants. Our finding that Aspm and Wdr62 function together to promote centriole duplication provides a novel insight into how defects in centriole biogenesis may underlie the pathogenesis of MCPH.…”
Section: Discussionmentioning
confidence: 72%
“…Wdr62 −/− and Wdr62 −/−; Aspm +/− mice analyzed at E12.5 for mitotic spindle orientation using conventional 2D microscopy as well as a 3D en face technique in flat-mount cortex (Juschke et al, 2014) did not show consistent changes in mutants. We found that spindle orientation in the mutants was not significantly different from controls in anaphase (Figure 2H), indicating that spindle orientation changes are unlikely to explain the microcephaly in these mutants.…”
Section: Resultsmentioning
confidence: 92%
“…As two-dimensional analysis of the spindle axis can lead to systematic measurement errors (Juschke et al 2014), metaphase and anaphase apical progenitors were imaged by spinningdisc confocal microscope, and axis orientation was determined in three dimensions. The angle between the line bisecting both spindle poles (mitotic centrosomal marker, Aurora A) and the plane of the ventricular surface was measured in E13.5 brain sections ( Fig.…”
Section: Chromatin Bridges In Ncaph2 Apical Neural Progenitors Lead Tmentioning
confidence: 99%
“…line, was used as the reference, as reported (Juschke et al, 2014). Further details can be found in the supplementary Materials and Methods.…”
Section: Mitotic Spindle Orientationmentioning
confidence: 99%